Thyroid hormones and their receptor gene expression as biomarkers of endocrine disruption in harbour seals (Phoca vitulina) - Tabuchi, Maki (2006)
Persistent organic pollutants (POPs) are ubiquitous environmental contaminants that are lipophilic, slow to degrade, bioaccumulate in aquatic food webs and threaten the health of both humans and wildlife. Predatory marine mammals, such as harbour seals (Phoca vitulina), are at particularly risk for the accumulation of high POP concentrations and resultant increased risk of toxic effects. EIevated levels of certain POPs have been implicated in the disruption of the endocrine system in marine mammals. The main purpose of this study was to assess whether current levels of POP are affecting thyroid hormone physiology of free-ranging harbour seals (Phoca vitulina) in British Columbia (BC), Canada and Washington State (WA), U.S.A. TH functions mainly by binding to nuclear thyroid hormone receptors (TRs) in target tissues and modulating specific gene expression programs. TR isoforms α (TRα) and β (TREβ) from harbour seals were isolated and quantified in internal and external organs. Harbour seals inhabiting industrialized regions exhibited a contaminant-related increase in blubber TRa and a decrease in circulating total thyroxine (TT4) concentrations. Our TRa expression results provide evidence of contaminant-related disruption of TH action at the Ievel of regulation of gene expression. Our findings of a metabolically active blubber layer. and a contaminant-related disruption of blubber TRa expression, suggest that, in addition to disruption of normal development, contaminant exposure could have important implications for lipid metabolism in seals. Consequently, the disruption of blubber TRa expression could influence such critical life processes as energy storage, thermoregulation, and buoyancy in marine mammals. In this study, the use of gene expression biomarkers in combination with a biopsy-based sampling approach was successfully applied to a small marine mammal (i.e. harbour seal) and demonstrates great promise for investigations in other sentinel species (i.e. cetaceans).